Análisis de la evolución e impacto del tratado Comunidad Andina de Naciones en los sectores más influyentes de la economía colombiana en el periodo de 2009-2019 (2020)
The present monograph tries to make an analysis of the behavior of the economy internally and externally of Comunidad Andina de Naciones treaty; for which the period from 2009 to 2019 is taken as a study reference. The analysis to carry out the study of the evolution of the treaty to work in the agreed period, was carried out through a focus on the economic and social aspect, for which The most significant events in this period and their implications in the aforementioned fields stand out, determining some important impacts brought about by the 2009 crisis in the economy of the member countries, the actions to follow that would be taken as a future plan for these repercussions in their economies. Following this analysis, the study of the most representative economic sectors for each member country of this treaty to work was chosen, where 3 key historical points will be selected to determine the evolution of these sectors and the changes made throughout the so-called Andean pact and to end this project we sought to carry out a study and analysis of exports and imports both intra and extra CAN in more detail to confirm the finding of the previous chapter, identifying that the most representative economic sector for CAN and also for the Colombian economy, was that of crude oil or bituminous mineral oils. The study shows that Colombia has little diversity of products to export and the production of manufacturing products must be improved so that participation in export lines improves both intra-can and extra-can.